Revitalisasi Pengelolaan Sumber Daya Manusia melalui Sistem Informasi Terintegrasi - Indrawati, Indrawati; Mintawati, Hesri; Simangunsong, Bonse Aris Mandala Putra; Azzahra, Vinsa; Apriansyah, Arip; Arfayan, Elly; P, Bintang Betari (Neolectura, 2023)
This research aims to present an in-depth review of the revitalization of human resource management (HR) through the implementation of integrated information systems (SIT) in a modern organizational environment. Through a comprehensive literature analysis, we explore the effectiveness, benefits, and challenges associated with SIT integration in HR management. The research method used involved a systematic review of various journal articles, books and related reports. The research results show that the application of SIT in HR management can improve operational efficiency, data-based decision making, and the overall quality of HR services. Nonetheless, challenges such as resistance to change, data security issues, and the complexity of technology integration remain major concerns. This research also presents practical recommendations for organizations that wish to successfully adopt and implement SIT in the context of HR management.